Attitudes of Libyan dental and medical students toward the use of English language as a medium of instruction - Khadeja Mojtaba Ahmed; Syed Wali Peeran; Mona Abdussalam Qasem Ahmed (Wolters Kluwer Medknow Publications, 2015)
Introduction: The use of English as a medium of instruction in the medical and dental schools in Sebha University, Libya has been officially acknowledged for more than 10 years ago; however, given the fact that Libyan students begin their English language learning at a relatively late age, some of them might face difficulties in their academic studies. Furthermore, the question of whether or not Libyan students prefer to be taught in English only has not been answered yet. Objectives: This study aims to find out whether Libyan medical and dental students prefer the use of English as a medium of instruction during their study at Sebha University or not. Methods: A total of 254 Libyan medical and dental students were surveyed. The participants were administered a questionnaire comprised of 18 multiple-choice questions. At the end of the questionnaire the students were asked to write a short paragraph about themselves. The responses of the participants were analyzed and compared using Chi square test. We assume that teaching core subjects in English only might be challenging to students since they lack proficiency in English as a result of learning English at a late age. Results: The results of this study show that the majority of the students surveyed prefer that core subjects be taught in both Arabic and English as this can facilitate the understanding of the material and enables them to improve their English language skills at the same time. Hence, the results of the study support our assumption. Conclusion: The present study provides an insight into the way Libyan medical and dental students view the use of English language as medium of instruction. According to students' views, the use of both students' native and target languages in teaching core subjects can be beneficial in terms of materials comprehension and language skills improvement.